Peningkatan Profesionalisme Guru IPA MGMP Kota Semarang melalui Pelatihan Modul Ajar berbasis TPACK - Novi Ratna Dewi; Prasetyo Listiaji; Trida Ridho Fariz; Luthfi Hanum Saputri; Bunaya Hanif Wintribrata; Meutia Salwa Aisy Nabilla; Putri Ulyatun Niswah; Ismida Rahmawati; Iqbal Fathurrohman; Faiq Hisyam Hartanto (Universitas Negeri Semarang, 2023)
The implementation of the Kurikulum Merdeka aims to improve the previous curriculum by implementing various intra-curricular learning. In the implementation of the independent curriculum, science teachers are required to develop innovative teaching modules so that the subject matter can be conveyed properly. Teaching modules must also be in line with the demands of the 21st century which require ICT integration. However, in its implementation there are several obstacles, one of which is the large number of science teachers who do not fully understand how to compile good teaching modules according to the context, characteristics, and needs of students in line with 21st century learning trends. In addition, only a small proportion of science teachers have used technology integration in the preparation of teaching modules due to lack of mastery of TPACK. Based on the problems faced by these partners, the service team felt the need to carry out activities to increase the professionalism of the Semarang City MGMP Science teachers through Assistance in the Preparation of TPACK-based teaching modules. This service activity is carried out in on with the implementation of the equivalent of 32 hours of study.